The Double-Edged Sword of Reflective Pondering: The Role of State and Trait Reflective Pondering in Predicting Depressive Symptoms Among Women With Breast Cancer. Issue 4 (20th August 2020) - Wang, Ashley Wei-Ting; Chang, Cheng-Shyong; Hsu, Wen-Yau
Abstract: Background and Purpose: Prior research has debated whether reflective pondering is a more constructive form of rumination than brooding, which is generally considered maladaptive. This study sought to investigate whether reflective pondering predicts depressive symptoms and whether reflective pondering is adaptive under certain conditions. We predicted that the effectiveness of reflective pondering could depend on concurrent coping strategies and the trait–state distinction. Method: Women with breast cancer ( N = 309; M age = 47.5) were assessed at four waves over 2 years. A time-lagged design was applied, with rumination (i.e., brooding and reflective pondering) and coping (i.e., engagement and disengagement) measured from T1 to T3, predicting depressive symptoms assessed from T2 to T4. These variables were measured by the Ruminative Response Scale, the Brief COPE, and the Hospital Anxiety and Depression Scale. Results: Using hierarchical linear modeling, brooding, but not reflective pondering, predicted elevated depressive symptoms at both between- and within-person levels. The relationship between reflective pondering and depression was moderated by the coping strategies. Individual differences in reflective pondering predicted worse depressive symptoms, but higher use of engagement coping mitigated the detrimental effect. Within individuals, the co-occurrence of reflective pondering and disengagement coping predicted a subsequent decrease in depressive symptoms. Conclusions: The emerging role of reflective pondering in the face of breast cancer-related stress appears to be a double-edged sword. Its impact on depression may depend on concurrent coping strategies and whether reflective pondering is assessed at state and trait levels. Abstract : Trait reflective pondering predicts increase in depression for individuals who endorse low active coping. However, when individuals endorse passive coping, state reflective pondering may be best described as benign.